Effect of plateletpheresis on haematological values in voluntary donors: a retrospective data analysis over an eight-month period - Gorana Ahmetović-Karić; Elma Ćatović-Baralija; Kenan Mehić (Medicinski glasnik, 2023)
Aim: To analyse changes in haematological values after plateletpheresis in donor population with regard to donor safety. Methods: A retrospective study was conducted on first time and repeated healthy donors over a period of eight months in the Blood Transfusion Institute in the Federation of Bosnia and Herzegovina in Sarajevo. A total of 75 plateletpheresis procedures performed using Amicus continuous flow cell separator were evaluated. Various pre- and post-donation haematological values were measured in all donors: haemoglobin concentration (Hb), haematocrit (Hct), red blood cell count (RBC), platelet count (PLT), white blood cell count (WBC), mean platelet volume (MPV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), and mean corpuscular haemoglobin concentration (MCHC). Results: A significant decrease in post-donation Hb, Hct, RBC, PLT, MCHC (p<0.000) and WBC (p=0.003), and a significant increase in MPV (p=0.011) and MCV (p<0.000) was found. Percentage reduction of haematological parameters Hb, Hct, RBC, PLT, WBC and MCHC decrease of 6.6%, 6.5%, 5.9%, 24%, 4.6% and 0.3%, respectively, in their respective count was noted postdonation. Eight (11%) donors had a post-procedure platelet count less than 150x10e9/L. Twenty two donors (29%) experienced mild side effects due to hypocalcaemia. Conclusion: Plateletpheresis procedures are generally safe and well tolerated, without evident associated clinical manifestations on healthy donors.
Keywords: complete blood count; cell separator; donor safety